Invisibility of Rural Schools in Teacher Training - Silvia Anzano Oto; Sandra Vázquez Toledo; Marta Liesa Orús (Universidad Autónoma de Baja California, 2022)
Initial teacher training is essential for future job performance in any teaching position. However, rural schools remain frequently overlooked. To address this issue, this research explores content specifically relating to rural schools in initial teacher training. An exhaustive review was carried out of the curricula, verification reports, and teaching guides of teaching degrees in public and private universities in Spain. The results show that rural schools are lacking in the educational skills teachers must acquire in their university education, with few courses specifically dealing with this type of school. In particular, we conclude that rural school training is essential due to the specific nature of these schools and there is a need to include this in teacher training, as some universities are already doing.